Comparative Evaluation of MTA and Biodentine as a Restorative Material In Deciduous Teeth - Sravani Uppala (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Several medicaments have been used in pulpotomy procedures of primary teeth. The present study was conducted to compare MTA with biodentine as a restorative material in deciduous teeth. Materials & Methods: Specimens were prepared with MTA (group-I) and Biodentine (Group-II) with mold with 10 in each group using stainless steel ring molds. Polyethylene tubes of 1 mm long were filled with MTA and biodentine and placed in flasks containing 10 ml distilled water at 37°C. After 2 h, the flasks were removed from hot air oven, and the water was assessed for pH. Results were tabulated and subjected to statistical analysis. Results: Each group had 20 teeth sample. In group I, MTA was used and in group II, biodentine material was used. The mean solubility value of MTA at 1st day was 1.55, at 4th day was 1.64, at 12thday was 2.15, at 30th day was 2.57 and at 45th day was 2.60. Similarly in group II at 1st day was 1.89, at 4th day was 2.11, at 12thday was 2.80, at 30th day was 3.61 and at 45th day was 5.34. pH at 2 hours was 9.28 in group I and 8.98 in group II, at 12 hours was 9.26 in group I and 9.39 in group II, at 24 hours was 9.20 in group I and 9.64 in group II, at 7 days was 8.76 in group I and 8.27 in group II, at 28 days was 7.62 in group I and 7.78 in group II. The difference was significant (P< 0.05). Conclusion: Authors found that both materials can be used in deciduous teeth. However, biodentine revealed higher solubility and pH as compared to MTA in deciduous teeth.